Diffusion of Clostridium perfringens NetB positive strains in healthy and diseased chickens - Drigo, Ilenia; Agnoletti, Fabrizio; Bacchin, Cosetta; Guolo, Angela; Cocchi, Monia; Bonci, Michela; Bano, Luca (Italian journal of animal science, 2009)
For over 30 years α toxin was considered the key virulence factor responsible for the appearance of necrotic enteritis (NE) in chickens but, recently, a new toxin related to the occurrence of NE, called NetB, has been described. The aim of this work was to evaluate the CP toxin-type and the NetB gene presence in strains collected from chickens affected or not by enteric diseases. 107 strains were tested: 30 isolated from chickens affected by NE, 54 from subjects affected by other enteric pathologies and 22 from healthy animals. All strains resulted toxin-type A and 26.17% of these was positive also for β2 toxin gene. No strains were positive for cpe gene. 27% (29/107) of CP was NetB positive and 93% (27/29) of these was isolated from birds affected by intestinal disorders. 16 NetB positive strains were obtained from chickens affected by NE (16/30), 9 from animals affected by other intestinal disorders (9/54) and 4 from healthy animals (4/22). A significant difference between the number of NetB positive strains isolated from animals affected by NE and healthy chickens has been observed (P=0.014). However, the finding that the 17.4% of strains isolated from healthy chickens was also positive for NetB, confirm that other virulence factors could play an important role on NE appearance.